The Effect of Dividend Payout Ratio, Net Profit Margin, and Return on Assets on The Growth of Income (Case Study On Coal Mining Sector Companies Registered in Indonesia Stock Exchange Period 2017-2019) - Sigit Prabowo (Quantitative Economics and Management Studies, 2020)
The purpose of this study was to determine whether there was an influence between DPR, NPM, and ROA on company profit growth. The population used is coal mining companies listed on the Indonesia Stock Exchange, consisting of 17 companies with 3 periods, namely 2017-2019. The sampling technique is done by means of saturated samples or census samples, in which the entire population is used as the sample. The data in this study are secondary data. Data analysis used multiple linear regression using SPSS. Tests were carried out using a significance level of 0.05. The results of the partial DPR research show a regression coefficient of 0.073 (positive) with a sig value (0.999), meaning that it has a positive and insignificant effect on profit growth. The results of the research in partial NPM show a regression coefficient of 447.313 (positive) with a sig value (0.000) which means that it has a significant positive effect on profit growth and the results of the research in partially ROA show a regression coefficient of 340.076 (positive) with a sig value (0.007) which means that it has a significant positive effect. on profit growth.